Microfaunal Assemblages and microfacies of Nummulitic Limestone of Naopurdan Group from Chwarta Area, Sulaimaniya Governorate, Northern Iraq - Daoud, Hyam Saleh (Sulaimani Journal for Pure and Applied Sciences, 2019)
Thirty-one samples were collected from nummulitic limestone of the Naopurdan Shaly Group of Paleocene-Early Eocene at the northern part of Chwarta town. Thirty-three thin sections were prepared and analyzed under a binocular microscope. Four main depositional microfacies Packstone, Floatstone, Boundstone, and Wackestone have been recognized. Thirty-two species of benthic foraminifers and algae were recorded; most of them were identified for the first time. The new species of microfossil assemblages identified comprises Nummulites sp., N. kdjokdjokartae, N. globulus, N. mammilatus, N. subirregularis, Alveolina violae, A. stercusmuris, A. frumentiformis, A. fornasinii, A. cf. sakaryaensis, Assilina laminose, A. granulosa, Discocyclina ranikotensis, D. dispansa, Lepidocyclina sumatrensis, L. parva, Cuvillierina sireli, Thalmanitta madrugaensis, Nephrolepidina sp., Idalina sinjarica, Cymopolia ellongata, Quinqueloculina, Biloculina, Pseudohatigerina sp., Asterocyclina ferrandezi n. sp. and Eulepidina dilatata. Besides these species, nine levels of distribution of microfauna were established and based on the microfossil assemblages and microfacies, the new paleoenvironments of deposition from the subtidal to outer ramp have been determined. In addition, the age Late Paleocene (Selandian) to Early Eocene (Lower Lutetian) was confirmed.
Keywords: Large foraminifera microfacies Paleocene Eocene Paleoenvironment